Cookie dough functional properties of partially replaced all-purpose wheat flour with powdered fruit skins and the hedonic perception of the resulting cookies - Al-Marazeeq, Khaled; Saleh, Mohammed; Angor, Malak; Lee, Youngseung (Frontiers in Sustainable Food Systems, 2024)
Investigating the functional properties of treated flour composites derived from fruit by-products of avocado (Persea americana), kiwifruit (Actinidia deliciosa), pineapple (Ananas comosus), and pomegranate (Punica granatum) skins, peels, and/or seeds combined, aiming to understand their stability and potential applications in food products.Fruit by-product flours were used to replace all-purpose wheat flour in ratios of 5%, 10%, 15%, and 20%. The treated flours were evaluated for physicochemical characteristics and used in cookie preparation, with 100% all-purpose wheat flour as the control.The water holding capacity (WHC) of composite flours increased with higher substitution levels, regardless of the holding temperature (25, 35, 45, and 55 °C), with the most significant increase observed in pomegranate treatments. Furthermore, freeze-thaw stability and viscoelasticity characteristics generally decreased for all composite flours compared to the control, likely due to gluten content dilution. The activation energy of the treated flours ranged from 11.1 to 62.0 kJ/mol. Therefore, gelatinization properties, formulation, and processing were affected by temperature variations due to viscosity dependence and activation energy requirements. Consumer testing indicated that cookies made with fruit by-product flours had an acceptable overall liking score of more than 6 out of 9.Overall, the results suggest that utilizing fruit by-products for treated flours can offer valuable natural sources of nutrients with enhanced functional properties, highlighting potential benefits for various food products.